2004
DOI: 10.1364/ol.29.000038
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations at high temperatures of long-period gratings written in germanium-free air–silica microstructure fiber

Abstract: We report what is to our knowledge the first characterization at high temperatures of long-period fiber gratings written in Ge-free air-silica microstructure fiber. The gratings written with the electric-arc technique suffer a low shift of the resonance wavelengths when the temperature is increased from 20 degrees C to 1200 degrees C. This shift is studied and compared with that of a long-period fiber grating written in a standard single-mode fiber by the same technique. Good thermal stability of the grating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…These structures written with CO 2 laser were proposed as strain-insensitive high-temperature PCF sensors (Zhu et al, [36]). For high-temperature applications, LPGs written in PCF with the electric arc technique have also shown an adequate performance, as was reported by Humbert et al [37].…”
Section: Pcf Sensing Based On Long-period Fiber Gratingssupporting
confidence: 54%
“…These structures written with CO 2 laser were proposed as strain-insensitive high-temperature PCF sensors (Zhu et al, [36]). For high-temperature applications, LPGs written in PCF with the electric arc technique have also shown an adequate performance, as was reported by Humbert et al [37].…”
Section: Pcf Sensing Based On Long-period Fiber Gratingssupporting
confidence: 54%
“…Based on the coupled local-mode theory, we analyze the coupling behavior and spectral characteristics of this type of structural LPGs, which are supported by experimental results. The permanent structural LPGs in the pure silica PCFs are expected to have high thermal stability and of interest for use as devices and sensors for operation in high-temperature environments [21,22]. The hole-drilling may also be used to fabricate fiber grating devices in other types of optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…These structures written with CO 2 laser were proposed as straininsensitive high-temperature PCF sensors (Zhu et al, 2005). For high-temperature applications, LPGs written in PCF with the electric arc technique have also shown an adequate performance, as was reported in (Humbert et al 2004). Wang et al also proposed an dipper characterization of the strain and temperature sensitivity as function of the external grooves created by focused CO 2 laser (Y. .…”
Section: Applications Of Lpgs In Pcfsmentioning
confidence: 76%
“…In this section a brief review of the main applications of LPGs in PCFs is presented. Concerning the temperature dependence of LPGs in IG-PCF, most of the papers report that temperature sensitivity is of the order of few picometers (up to 10) per degrees centigrade (Dobb et al, 2004;Petrovic et al, 2007;Zhu et al 2005;Humbert et al, 2004) while the sensitivity of gratings in SMF is reported to be in the range 30-200 pm/°C or more (James & Tatam, 2003;Rego et al 2005b). The shifts of LPG bands due to thermal changes is principally attributed to two factors such as the thermooptic effect and the thermal expansion of the fiber that force wavelength shifts of opposite signs (Petrovic et al, 2007).…”
Section: Applications Of Lpgs In Pcfsmentioning
confidence: 99%